Analisis Konflik Pengelolaan Sumberdaya Alam di Kawasan Taman Nasional Gunung Gede Pangrango (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2018)
Conflict canâ€™t be separated from the activity of community life and both are integrated. Humans will make efforts in order to fulfil their needs, including in terms of natural resources. Conservation areas or better known as the national park is one of the areas most prone to conflict over natural resources. This study aimed to analyze the reality of conflict, the factors causing conflicts, the impact of conflict, the relationship of factors causing conflict with the intensity of emerging conflict and the forms of conflict resolution in the park area. This research is quantitative research was supported by qualitative data with the instrument questionnaires and in-depth interview guide. The problem between farmers and the park is caused by the change of status of Perhutani area into Gunung Gede Pangrango National Park. This transformation changed the rules of the people who initially worked on the land in the region to be stalled. The conflicts natural resource issues until 2016 increasingly complex due to intimidation received by farmers every year. In resolving conflicts, researchers provide the idea of Community Based Conflict Management (CBCM) as a method of reducing conflict.Keywords: Analysis of conflict, natural resources, national parksABSTRAKKonflik tidak bisa dipisahkan dari aktivitas kehidupan bermasyarakat dan keduanya saling berintegrasi. Manusia akan melakukan berbagai usaha agar kebutuhan hidupnya dapat tercukupi termasuk dalam hal sumberdaya alam. Kawasan konservasi atau yang lebih dikenal dengan sebagai taman nasional merupakan salah satu daerah yang paling rawan terjadi konflik sumberdaya alam. Penelitian ini bertujuan untuk menganalisis realitas konflik, faktor-faktor penyebab konflik, hubungan faktor-faktor penyebab konflik dengan intensitas konflik emerging dan gagasan penyelesaian konflik di kawasan Taman Nasional Gunung Gede Pangrango. Jenis penelitian ini adalah penelitian kuantitatif didukung oleh data kualitatif dengan instrumen kuesioner dan panduan wawancara mendalam. Permasalahan antara petani penggarap dengan pihak taman nasional disebabkan oleh adanya perubahan status kawasan Perhutani menjadi Taman Nasional Gunung Gede Pangrango. Perubahan ini merubah landasan pijak masyarakat yang awalnya menggarap lahan di kawasan menjadi terhenti. Konflik permasalahan sumber daya alam hingga Tahun 2016 semakin kompleks akibat adanya intimidasi yang diterima petani setiap tahunnya. Dalam menyelesaikan konflik, peneliti memberikan gagasan Manajemen Konflik Berbasis Komunitas (CBCM) sebagai metode peredam konflik.Kata Kunci: Analisis konflik, sumberdaya alam, taman nasionalÂ